A constitucionalidade do poder de investigação do Ministério Público - Martins, Dyeilisson Baumgardt (My University, 2024)
The purpose of this Course Conclusion Work is to determine whether the investigative power exercised by the Public Prosecutor's Office is in accordance with the provisions contained in the Federal Constitution of 1988. The deductive method of approach is used, while the applied technique is bibliographic research, doctrinal and jurisprudential. In its development, it addresses positive questions brought by jurists about the recognition of the legitimacy of the Investigative Power of the Public Ministry, such as, for example: the greater effectiveness of the Public Ministry in elucidating the cases for also being the accuser in the criminal action to be, possibly , established in the future; and the confidence that Brazilian society places in the MP and the reflex that this would have in the criminal investigation. On the other hand, we have the harms brought by some lawyers such as excessive publicity that may harm the investigated, the MP's partiality for being also the accuser in the criminal action, the MP's facility to manipulate the evidence collected and the possibility to judge based on exclusive in the evidence brought by the Public Ministry. After that, it also brings the constitutional arguments that meet and recognize the MP's Investigative Power. And, finally, the need to amend CF / 88 to prohibit or expressly allow the Public Ministry to initiate investigative procedures. [resumo fornecido pelo autor]
O presente Trabalho de Conclusão de Curso tem por objetivo determinar se o poder de investigação exercido pelo Ministério Público está de acordo com as determinações contidas na Constituição Federal de 1988. Tem por método de abordagem o dedutivo, enquanto a técnica aplicada é a pesquisa bibliográfica, doutrinária e jurisprudencial. Em seu desenvolvimento, aborda questões positivas trazidas por juristas sobre o reconhecimento da legitimidade do Poder de Investigação do Ministério Público, como, por exemplo: a maior efetividade do Ministério Público na elucidação dos casos por também ser o acusador na ação penal a ser, possivelmente, instaurada futuramente; e a confiança que a sociedade brasileira deposita no MP e o reflexo que isso teria na investigação Penal. Por outro lado, aborda os malefícios trazidos por alguns juristas como a publicidade excessiva que poderá prejudicar o investigado, a parcialidade do MP por ser também o acusador na ação penal, a facilidade de o MP manipular provas colhidas e a possibilidade de se julgar com base exclusiva nos indícios trazidos pelo Ministério Público. Depois disso, traz, também, os argumentos constitucionais que vão ao encontro e de encontro ao reconhecimento do Poder Investigatório do MP. E, por fim, a necessidade de se emendar a CF/88 para proibir ou permitir expressamente que o Ministério Público instaure procedimentos investigatórios. [resumo fornecido pelo autor]
Keywords: Ministérios públicos; Investigação criminal; Brasil. [Constituição (1988)